Hysteresis Current Control with Input Filter Design for High Frequency Series Resonant Full Bridge Inverter - Debabrata Roy; Pradip Kumar Sadhu; Nitai Pal (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
This paper talks about the analysis of a high frequency series resonant inverter for using domestic and industrial induction heating purpose. It is a technique i.e. used for heat conductive materials hard and soft metals.  Series Resonant inverters which operate at high frequency preferable for induction heating which normally works in 5-55KHz. High frequency series resonant inverters which is made up of Insulated Gate Bipolar Transistor (IGBT). Power control is obtained by Hysteresis Current Control and filter design is incorporated in the input power supply. Soft switching techniques is performed which minimizes switching losses and proper filter design minimizes harmonic injection in the power supply.